Realizing Maqasid al-Shari‘ah in Islamic financial institutions: Contemporary challenges and strategic reforms - Wan Yussof , Wan Nor Aisyah; Mansor , Nuruul Hidayah; Bahori, Adibah; Mohd Noh, Nur Syahirah; Husin, Muhammad Noor (Journal of Islamic, Social, Economics and Development, 2025)
Islamic financial institutions (IFIs) are established on Shari‘ah principles, aiming to achieve the higher objectives of maqasid al-Shari‘ah, which focus on justice, welfare, and ethical integrity. However, despite the rapid global growth of Islamic finance, the actual realization of these objectives remains suboptimal. The objectives of the study are to examine the challenges in implementing maqasid al-Shari‘ah, assess the gaps between Shariah compliance and maqasid attainment, and propose strategies for enhancing integration through regulatory, governance, and performance reforms. A qualitative synthesis of empirical and theoretical studies in Malaysia, along with cross-country analysis and a global survey, identifies three primary categories of challenges: (i) regulatory compliance constraints, (ii) operational practices that undermine the authenticity of maqasid, and (iii) governance weaknesses. The study's findings reveal a structural mismatch between the conventional regulatory framework and the requirements of Islamic ethics, as well as pragmatic approaches to product and governance conflicts. The study suggests integrating maqasid-based objectives into regulatory frameworks, broadening Shariah audits to encompass ethical and social aspects, improving leadership capabilities in maqasid governance, and implementing standardised metrics for maqasid performance. This study enhances theoretical and practical knowledge by providing a systematic analysis of the disparity between Shariah compliance and maqasid attainment, while emphasising strategic pathways for future reforms.